Efficient removal of NaOl from mineral processing wastewater using Al-electrocoagulation. (15th July 2023) - Jing, Gaogui; Meng, Xiangsong; Zheng, Renji; Chen, Jing; Sun, Wei; Gao, Zhiyong
Abstract: Sodium oleate (NaOl) is widely used as collector for oxidised ore flotation, and residual NaOl in mineral processing wastewater is a serious threat to mine environment. In this work, the feasibility of electrocoagulation (EC) as an alternative for chemical oxygen demand (COD) removal from NaOl-containing wastewater was demonstrated. Major variables were evaluated to optimise EC, and related mechanisms were proposed to interpret the observations in EC experiments. The initial pH of the wastewater greatly affected the COD removal efficiency, which was likely to be related to the variation of predominant species. When the pH was below 8.93 (original pH), liquid HOl(l) was the predominant specie, which could be rapidly removed by EC thought charge neutralisation and adsorption. At original pH or higher, Ol − could react with dissolved Al 3+ to form insoluble Al(Ol)3, which was subsequently removed through charge neutralisation and adsorption. The presence of fine mineral particles could reduce repulsion force of the suspended solids and promote flocculation, whereas the presence of water glass had an opposite effect. These results demonstrated that EC can be employed as an effective process to purify NaOl-containing wastewater. This study will contribute to deepening our understanding of EC technology for NaOl removal and provide useful information to researchers in mineral processing industry. Highlights: EC for NaOl-containing mineral processing wastewater treatment was systematically studied. Removal of NaOl resulted from complexation and adsorption to generated flocs. Fine mineral particles could drive the occurrence of flocculation, whereas the water glass possessed an opposite effect. EC was found to be a feasible NaOl removal technique applied to mineral processing wastewater.